Evaluation of hygienic-sanitary conditions of hospital nutrition and dietary services from the perspectives of internal and external auditors - Lize Stangarlin (Food Science and Technology, 2013)
The objective of this study was to evaluate the hygienic-sanitary conditions of hospital nutrition and dietary services using external and internal auditors. Eleven hospitals were evaluated for their nutrition and dietary services using an evaluation checklist based on food safety requirements in the current legislation. The checklist was applied by an internal auditor (a technical supervisor) and an external auditor (a professional with experience in food services) between August and October 2011. According to the number of items on the evaluation checklist that were considered adequate, the hospital facilities were ranked as excellent, good, regular, bad, or very bad. The results obtained by the auditors were compared. According to these results, it can be said that most of the hospital nutrition and dietary services were rated as good for overall quality by the internal auditor, while the external auditor classified them as Regular. There was a clear difference between the evaluations of the auditors, both in terms of the number of items considered adequate and the overall requirements' average score. It can be concluded that hospital nutrition and dietary services should meet safety requirements in order to provide food. These facilities should have external audits conducted as a way to prevent routine problems from being perpetuated.